Aedes aegypti and dengue virus investigation of anatomic, genomic, and molecular determinants of vector competence - Bernhardt, Scott Arthur, author; Blair, Carol D., advisor; Black, William C., IV, advisor (Colorado State University. Libraries, 2009)
Dengue (DENV) causes one of the most rapidly expanding diseases in the tropics. Vector competence (VC) in Aedes aegypti for DENV-2 is a quantitative trait and has been shown to be highly variable. Questions remain as to whether variation in VC continues to exist after the primary field observation. What genetic factors contribute to VC and do these factors evolve from arbovirus exposure remain unclear.

To determine whether variation in VC phenotype is temporally stable which had previously been characterized, I collected Ae. aegypti eggs in 2005 from 19 sites in Mexico where VC had been studied previously and determined VC for DENV-2. VC in these collections ranged from 38-83%, the midgut infection barrier rates ranged from 930% and the midgut escape barrier (MEB) rates ranged from 7-36%. Spatial variations in VC continued to exist between collection sites; however, similar relative VC rates were found in specific sites when analyzed over time. During this study I also detected the presence of nuclear copies of mitochondrial DNA in Ae. aegypti.

I hypothesized that the RNAi and apoptosis pathways significantly contribute to DENV-2 VC in Aedes aegypti. We constructed an F1 intercross family using a P1 female from Aedes aegypti aegypti (Aaa) and a P1 male Aedes aegypti formosus (Aaf). Recombination rates in the F2 offspring were significantly reduced and genotype ratios suggested a deleterious recessive allele on chromosome 3. The F2 linkage map was incongruent with the established map for Aaa. Recombination rates and gene order were consistent with the presence of multiple chromosomal inversions in Aaf on all three chromosomes. Genotype-phenotype analyses demonstrated that the three RNAi pathway genes we examined significantly contribute to the MEB for DENV-2.

The final research aim was to determine the rate at which RNAi genes are evolving and to determine whether arbovirus infections contribute to RNAi evolution in Aedes aegypti. Sequence data were obtained from three RNAi genes and their three microRNA paralogs from 94 mosquitoes from five geographically widespread collection sites. Rates of non-synonymous to synonymous amino acid substitutions and phylogenetic analysis showed that the RNAi genes are evolving faster than their microRNA paralogs. A significant correlation was also identified between Aedes aegypti dcr2 average number of nucleotide differences and DENV-2 MEB.
Keywords: Aedes aegypti; chromosomal inversions; dengue; mitochondrial insertions; RNAi; organismal biology; genetics; microbiology; entomology